Penataan Arsip Pada Kantor Desa Jembatan Basah,Kecamatan Bula Barat Kabupaten Seram Bagian Barat - Putri Andini Dameani; Vera Paulin Kay; Leonora Ferdinandus (Jurnal Administrasi Terapan, 2025)
The Jembatan Basah Administrative Village Office uses an alphabetical system for archiving, which the author observed was not yet effective. Although incoming and outgoing letters were recorded in an alphabetical order book, archive storage practices were not yet carried out neatly and orderly. The files are not labeled or alphabetically coded, making document searches inefficient, sometimes taking up to ten minutes, compared to the ideal time of less than one minute. Furthermore, storage facilities are very limited, as the files are placed in plain folders and stored in wooden cabinets that are also used for other items, creating a disorganized impression. This situation is exacerbated by the piles of mail scattered on the work desk, which impacts neatness and work effectiveness. Furthermore, The officers who handle archives still have limited competence because they only have a high school education background and have never received special training in the field of archives. The method used in this research was qualitative data analysis. Data were collected through direct observation at the research location and interviews with the village head and village officials involved in archives management. The data were then analyzed descriptively to illustrate the actual state of archives management at the Jembatan Basah Administrative Village Office and to identify the challenges encountered. The conclusion of this paper is that the archival management at the Jembatan Basah Administrative Village Office has not been implemented properly. The main problems identified include the absence of labels or alphabetical codes on archives, limited storage facilities, and a lack of competence among archivists. Therefore, it is necessary to improve the archive storage system, provide adequate facilities, and enhance the competence of human resources so that archive management can be more orderly, effective, and efficient. Keywords: Archive Arrangement, Alphabetical System